Akulturasi Islam dan Budaya Lokal terhadap Tradisi Mangaji Kamatian pada Masyarakat Lareh Nan Panjang Kabupaten Padang Pariaman - Edriagus Saputra Agus; Mhd. Zulfadli; Novizal Wendry; Dian Puspita Sari (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2021)
The tradition of mangaji during the death is a form of acculturation of Minangkabau culture and Islam, perceived as part of the prophetic traditions. However, some people interpret this tradition as bid'ah, and even, some others accused the practice as haram because it was part of jāhiliyyah traditions. This living hadith study is going to investigate the practice using a phenomenological approach during field research. The result of this study indicates the tradition of mangaji during the death in the Lareh Nan Panjang community is an acculturation between Islamic teachings based on the Qur'an and hadith. Historically mangaji refers to the interpretation of Shaykh Burhanuddin, a scholar who spread Islam in Padang Pariaman during the sixteenth and sevententh centuries. The syaikh changed the people’s habits of grieving at death with reciting verses of the Qur'an, ṣalāwāt, ẓikir, taḥlīl and prayers ‘led by tuangku or labai. These recitations have been compiled in the mangaji guidebook. In a nutshell, mangaji has many values including worships, educations, empathies, maintaining harmonies, helpings and caring, solidarities, brotherhoods and affections.